Analysis of Microbial load and Litter Characterisation of Araromi Beach Sand, Ondo State, Nigeria - O. S. Odewumi; M. M. Quist (Journal of Applied Sciences and Environmental Management)
Increasing development of coastal areas and recreational use of beaches, has been linked with greater threats associated with public health hazards with respect to sediment and sand present in these coastal areas. This study assessed the microbial and litter characteristics of Araromi Beach Sand, Ondo State, Nigeria using appropriate standard methods. Data obtained show that Twenty-nine microbes comprising 17 bacterial species, seven fungal species and five yeast species were isolated. The microbial load ranged from 1.45 × 10-4 CFU/g to 12.4 × 10-4 CFU/g which were found to be within the permissible limit (8 CFU/g to 250 CFU/g) as stated by the WHO. However, Microbial load showed significant difference (t=0.011) between the areas of high tourist activities and low tourist activities. Also, the beach sand litters were categorized into seven groups. However, the most common type of litter were Organic wastes in the form of dried leaves and tree branches (59%), followed by Plastic/Polystyrene (32%). The average litter density ranged from 10.00 litter/m2 in July to 21.57 litter/m2 in December. There was no provision for waste disposal and toilet facilities. Araromi beach falls under the Moderately Dirty category with Clean Coast Index values of 8.52 and 6.81 in the dry and wet seasons respectively. Overall, the results of this study shows that Araromi beach is still in an underdeveloped state with the host community the key contributors to the amount of waste found on the beach. It is therefore recommended that to attract more visitors and improve the overall beach experience, the local community and government should invest in regular beach clean-ups and waste management programs to keep the beach in a pristine condition.